Efficacy and safety of switching to abacavir/lamivudine (ABC/3TC) plus rilpivirine (RPV) in virologically suppressed HIV-infected patients on HAART. - Palacios-Muñoz, María Rosario; Pérez Hernández, Isabel Ascensión; Martínez, M.A.; Mayorga, María Luisa; González-Doménech, Carmen María; Omar, Mohamed; Olalla, Julián; Romero, Alberto; Romero, J.M.; Pérez Camacho, Inés; Hernández-Quero, José; Santos-González, Jesús Leandro (Springer, 2016)
We analysed the efficacy and safety of switching from a regimen based on nonnucleoside reverse transcriptase inhibitors (NNRTI) or integrase inhibitors (INI) to ABC/3TC + RPV in virologically suppressed HIV-infected patients. This multicentre, retrospective study comprised asymptomatic HIV-infected patients who switched from 2 NRTI + NNRTI or 2 NRTI + INI to ABC/3TC + RPV between February 2013 and December 2013; all had undetectable HIV viral load prior to switching. Efficacy and safety, and changes in lipids and cardiovascular risk (CVR) were analysed at 48 weeks. Of 85 patients (74.1 % men, mean age 49.5 years), 83 (97.6 %) switched from a regimen based on NNRTI (EFV 74, RPV 5, ETV 2, NVP 2), and 45 (53 %) switched from TDF/FTC to ABC/3TC. The main reasons for switching were toxicity (58.8 %) and convenience (29.4 %). At 48 weeks, 78 (91.8 %) patients continued taking the same regimen; efficacy was 88 % by intention to treat, and 96 % by per protocol. Two patients were lost to follow-up and five ceased the new regimen (4 due to adverse effects and 1 virologic failure). Mean CD4 cell counts increased (744 vs. 885 cells/μL; p = 0.0001), and there were mean decreases in fasting total cholesterol (-15.9 mg/dL; p < 0.0001) and LDL-cholesterol (-11.0 mg/dL; p < 0.004), with no changes in HDL-cholesterol, triglycerides, total cholesterol:HDL-cholesterol ratio, and CVR. ABC/3TC + RPV is effective and safe in virologically-suppressed patients on antiretroviral therapy (ART). Forty-eight weeks after switching the lipid profile improved with decreases in total and LDL cholesterol.
Keywords: Infecciones por VIH; Inhibidores víricos; HAART; HIV-1; Efficacy; ABC/3TC; RPV; Virologically suppressed; Safety; Switching; Abacavir/lamivudine; Rilpivirine